Elevated High Molecular Weight Fibrinogen in Plasma Is Predictive of Coronary Ischemic Events after Acute Myocardial Infarction - Reganon, Edelmiro; Vila, Virtudes; Ferrando, Fernando; Martínez-Sales, Vicenta; Fayos, Laura; Ruano, Miguel; Aznar, Justo (Thrombosis and Haemostasis, 1999)
This study investigates the association between the concentration and function of plasma fibrinogen molecules measured at the time of hospital admission in patients with acute myocardial infarction (AMI), with reference to the risk of new coronary ischemic events during a three-day follow-up period of. Before starting fibrinolytic and anticoagulant treatment plasma fibrinogen, high molecular weight fibrinogen (HMW-fibrinogen), fibrin formation rate (FbFR) and phosphorous content in fibrinogen were determined in 90 AMI patients. During a three-day follow-up period 12 patients suffered new ischemic events. The 12 patients with coronary ischemia had higher concentrations of plasma fibrinogen (312 ± 23 vs. 270 ± 73 mg/dl, p <0.05) and HMW-fibrinogen (246 ± 35 vs. 189 ± 23 mg/dl, p <0.001) and a higher FbFR (65 ± 30 vs. 40 ± 25, p <0.001) than patients without these events. No association was found between the phosphorous content in fibrinogen and new coronary ischemic events. We conclude that after myocardial infarction an elevated plasma level of HMW-fibrinogen and a high FbFR value at the time of hospital admission are associated with new coronary ischemic events during a three-day follow-up period.
Keywords: Fibrinogen; HMW-fibrinogen; fibrin; myocardial infarction; coronary ischemic events